The Role of English for the Improvement of Vocational High School Students in the Department of Accounting About Financial Reports - Aditama Melati; Nunung Suryati; Enny Irawati; Mutmainnah Mustofa (Owner : Riset dan Jurnal Akuntansi, 2023)
Vocational high school students really need to master English because to improve and understand the processes in accounting financial reports because every transaction in the accounting department uses English so that students' abilities in English increase even more and students understand and know about transactions related to the company's financial reports from the research results there are still many students who do not understand and do not understand English, it can be shown from the results of the average score of students in the subject of English is still low the type of research is that which is used descriptive qualitative. As well as the method in this research is an observational interview test, as well as the results of the research that has been carried out, namely from the results of student activities from start to finish, namely with the initial test cycle to the final test by looking at the increase in the average value of students in class in each process activity, namely the learning outcomes of vocational high school students by understanding accounting readings in English. Keywords: English, vocational high school students majoring in accounting, financial reports